2018
DOI: 10.3748/wjg.v24.i47.5297
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C: From inflammatory pathogenesis to anti-inflammatory/hepatoprotective therapy

Abstract: Hepatitis C virus (HCV) infection commonly causes progressive liver diseases that deteriorate from chronic inflammation to fibrosis, cirrhosis and even to hepatocellular carcinoma. A long-term, persistent and uncontrolled inflammatory response is a hallmark of these diseases and further leads to hepatic injury and more severe disease progression. The levels of inflammatory cytokines and chemokines change with the states of infection and treatment, and therefore, they may serve as candidate biomarkers for disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 134 publications
(167 reference statements)
0
69
1
9
Order By: Relevance
“…34 If not promptly treated, hepatic C virus infections progressively evolve from chronic inflammation to fibrosis or to even more severe disease progression (eg, cirrhosis and hepatocellular carcinoma). 35 In particular, the early detection of diffusive liver disorders (acute hepatitis and early In conclusion, this study proved that accounting for pseudo-diffusion intravoxel dephasing affects the estimation of the diffusion tensor metrics in both liver and kidneys. In the liver, mesoscopic fluid movements (due to blood or bile flow) may be at the origin of the pseudo-diffusion dynamics.…”
Section: Figurementioning
confidence: 54%
“…34 If not promptly treated, hepatic C virus infections progressively evolve from chronic inflammation to fibrosis or to even more severe disease progression (eg, cirrhosis and hepatocellular carcinoma). 35 In particular, the early detection of diffusive liver disorders (acute hepatitis and early In conclusion, this study proved that accounting for pseudo-diffusion intravoxel dephasing affects the estimation of the diffusion tensor metrics in both liver and kidneys. In the liver, mesoscopic fluid movements (due to blood or bile flow) may be at the origin of the pseudo-diffusion dynamics.…”
Section: Figurementioning
confidence: 54%
“…In a recent article on HIV/HCV-coinfected patients, we showed that plasma biomarkers of bacterial translocation, in ammation, endothelial dysfunction, and coagulopathy increased with the increase of liver brosis severity, particularly in patients with LSM ≥ 40 KPa [36]. However, the eradication of HCV with antiviral therapy can stop this pathological process of the liver, at least almost entirely [35]. Additionally, the decrease in in ammation biomarker levels could also indicate a lower risk of developing comorbidities in cirrhotic patients who achieved SVR with DAA therapy [2,25].…”
Section: Discussionmentioning
confidence: 92%
“…Several reports have also shown a signi cant decrease in plasma biomarkers related to in ammation and immune activation after SVR with all-oral DAAs in HIV/HCV-coinfected patients [18,[30][31][32][33][34]. However, DAA therapy alone does not completely block uncontrolled in ammation and liver injury, particularly with advanced liver disease [35]. Thus, some cirrhotic patients who achieve SVR with DAAs remain at risk of cirrhosis progression and developing hepatocellular carcinoma [2].…”
Section: Introductionmentioning
confidence: 99%
“…Raltegravir is metabolized by hepatic glucuronidation primarily by UGT1A1. Inflammation associated with chronic HCV infection accelerates hepatocyte damage, and could affect liver uptake and reduce drug metabolizing enzyme activity, resulting in decreased clearance of drugs that undergo hepatic metabolism . HCV infection rapidly clears from the plasma and liver with DAA therapy .…”
Section: Discussionmentioning
confidence: 99%